Чужое терзанье: роман / Вэл Макдермид ; пер.с англ. И.Гиляровой - Макдермид Вэл (Лекарство от скуки, 2010)
Экземпляры: СФ-7 (20100914) / Инвентарный номер: 39054z7 / Цена: 292.60 / Сис.шифр: 84(4Вел) / Авт.знак: М 15 / ГРНТИ: 17.82.32 / ББК: 84(4Вел)